2004
DOI: 10.1089/105072504322880382
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends of Incidence and Prognosis of Thyroid Carcinoma in Lower Franconia, Germany, from 1981–1995

Abstract: Iodine prophylaxis does influence the distribution of the histologic types of thyroid cancer and leads to an increase in the ratio of papillary versus follicular carcinoma. Our study supports the hypothesis that the benefits of correcting iodine deficency outweigh the risks of iodine supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 31 publications
6
48
1
3
Order By: Relevance
“…The histological distribution of thyroid cancer in the present series was similar to that reported in iodine-sufficient areas, with a higher proportion of papillary thyroid cancer (76% over overall thyroid carcinomas). It represents the same pattern that was reported in the USA (Hundahl et al, 1998;Scheiden et al, 2006;Schlumberger et al, 2008) and some European countries (Blanco Carrera et al, 2005;Farahati et al, 2004;Sant et al 2003;Scheiden et al, 2006). Likewise, in our series the ratio papillary/follicular was high, which is the predominant pattern reported in the Western world (Sant et al, 2003;Teppo & Hakulinen, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…The histological distribution of thyroid cancer in the present series was similar to that reported in iodine-sufficient areas, with a higher proportion of papillary thyroid cancer (76% over overall thyroid carcinomas). It represents the same pattern that was reported in the USA (Hundahl et al, 1998;Scheiden et al, 2006;Schlumberger et al, 2008) and some European countries (Blanco Carrera et al, 2005;Farahati et al, 2004;Sant et al 2003;Scheiden et al, 2006). Likewise, in our series the ratio papillary/follicular was high, which is the predominant pattern reported in the Western world (Sant et al, 2003;Teppo & Hakulinen, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Chronic iodine deficiency has been associated with increased risk of follicular and anaplastic carcinoma, whereas iodine excess increased risk of papillary and decreased risk of follicular carcinoma (30)(31)(32). Several studies conducted in areas with previous iodine deficiency have reported a progressive increase in the ratio of papillary to follicular carcinoma after iodine prophylaxis (25,(33)(34)(35)(36).…”
Section: Thyroid Cancer Incidence Trend In Sao Paulo and Seermentioning
confidence: 99%
“…It has been hypothesized that iodine deficiency causes a high incidence of follicular tumors and that iodine supplementation shifts the distribution towards papillary tumors, as observed in Switzerland (70), Germany (77) and in Austria (78) (figure 1).…”
Section: Iodine Intake and Thyroid Cancermentioning
confidence: 99%